Paradoxical immune reconstitution inflammatory syndrome associated with disseminated tuberculosis infection in an unrelated donor cord blood transplant recipient. Issue 3 (3rd April 2018) - Lee, Yeon Joo; Bacchus, Melissa; Schmidt, Elizabeth; Chawla, Mohit; Barker, Juliet N.; Papanicolaou, Genovefa A.
Abstract: Tuberculosis (TB) is an infrequent infection after hematopoietic cell transplant (HCT), with associated mortality up to 30%. The utility of universal screening for latent TB in HCT candidates is controversial due to the lack of sensitive screening tests. We describe a case of disseminated TB infection complicated by immune reconstitution inflammatory syndrome in an adult double unit umbilical cord blood transplant recipient who originated from the United Arab Emirates.